Pengolahan Rebusan Daun Sirih (REDARIH) sebagai Upaya Menjaga Kebersihan Organ Reproduksi Wanita - Anjelaveronika, Anjelaveronika; Kabuhung, Elvine Ivana; Dona, Sismeri (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Reproductive organs are sensitive organs and require special care. Good care in maintaining the cleanliness of reproductive organs is beneficial in maintaining reproductive health. Maintaining the health of reproductive organs begins with maintaining personal hygiene, including vaginal hygiene which aims to keep the vagina clean, normal, healthy and free from the possibility of diseases including vaginal discharge. The use of boiled betel leaf water for women of childbearing age who experience symptoms of vaginal discharge has almost all had an effect on decreasing. The problems found in Sungai Tabuk Kota Village RT 03 & RT. 04, based on the results of the study, are the low knowledge of women about reproductive health and many women who do not care about the cleanliness of their own reproductive organs. One of the successes of community service activities is teaching the community to make boiled betel leaves by maintaining reproductive hygiene. The implementation of this service is by teaching mothers how to process boiled betel leaves (REDARIH) to maintain reproductive health. The target is all women of productive age to menopause in RT 03 & 04 in Sungai Tabuk Kota Village. The implementation of this program was carried out on Monday, August 19, 2024 at PAUD Ceria RT. 04 Tabuk River, Banjarmasin City at 10:00 WITA – finished. This activity was attended by community leaders, coordinating midwives, village midwives, health workers from the Health Center (program holders), village midwives, integrated health post cadres, mothers of productive age to menopause, mentors and also midwifery students.